Properties of composite laminates based on basalt fibers with epoxidized vegetable oils. (5th May 2015) - Samper, M.D.; Petrucci, R.; Sanchez-Nacher, L.; Balart, R.; Kenny, J.M.
Graphical abstract: Highlights: New environmentally friendly composites from biobased epoxies and basalt fibers. Improved performance with conventional silane treatment on basalt fabrics. Composites with excellent appearance due to basalt shiny brown color. Potential applications as substitute of glass fiber reinforced composites in engineering design. Processing with conventional resin transfer molding (RTM) techniques. Abstract: This paper deals with the development of polymeric materials derived from epoxidized vegetable oils which have been used in the manufacture of laminated composite materials with basalt fabrics. Epoxidized linseed oil (ELO) and epoxidized soybean oil (ESBO) were used as biobased matrices. The basalt fabrics were modified with amino-silane and glycidyl-silane to increase fiber–matrix interactions. The curing behavior of both resins was evaluated by differential scanning calorimetry (DSC) and oscillatory rheometry (OR). The evaluation of mechanical properties was made by tensile, flexural and Charpy tests. The extent of the fiber–matrix interactions among interface was evaluated by scanning electron microscopy (SEM). The obtained results revealed that surface modification of basalt fibers with glycidyl-silane clearly improves the mechanical properties of the composites. The use of the ELO resin as matrix for composite laminates improved substantially the mechanical performance compared to composites made with ESBO.